Using otolith weight to predict the age of different stocks of Sperata aor (Siluriformes: Bagridae) from the River Ganga - Nazir, Aafaq (2019)
Estimation of accurate fish age is considered as an essential step for the understanding of life history characteristics, population dynamics, and the management of the fisheries resources. The otolith weight keeps on increasing because of continuous deposition of material on the otolith surface; therefore, otolith measurements are successfully used to infer fish age. The present study was conducted to estimate the relationship between otolith weight and observed age (estimated by counting annuli on the sectioned otoliths) for the stocks of Sperata aor. A total of 315 samples were collected from January 2016 to April 2017 from three different stocks of S. aor i.e. Narora-Kanpur, Varanasi and Bhagalpur from the River Ganga. Linear regression analysis was applied between otolith weight and observed age to predict the age of the fish of each stock from otolith weight. Significant relationships between otolith weight and fish age were observed for the three stocks of the selected fish species from the River Ganga (R2 > 0.9, P < 0.001). No significant differences were found in the otolith weight among the stocks of S. aor (ANCOVA: F2,134 = 0.047; P > 0.05). Overall, 88.5, 88.8, and 87.2 % of the predicted ages were correctly classified to their observed ages for Narora-Kanpur, Varanasi, and Bhagalpur stock, respectively. Thus, it can be concluded that the relationship between otolith weight and fish age can provide a surrogate method of age estimation, and can be used to examine the age structure of the three stocks of S. aor from the River Ganga.